The Influence of Frontliner Employee Performance on Customer Satisfaction at Bank Sulselbar Major Branch of Palopo City - Nurhalisa Munawarah; Andi Aslinda; Aris Baharuddin; Haedar Akib; Risma Niswaty (Public Resource Innovation Management and Excellence, 2024)
This research examines the influence of Frontliner employee performance on customer satisfaction at Bank Sulselbar, the main branch of Palopo City. The purpose of this study was to determine the performance of employees at the bank of sulselbar the main branch of the city of palopo, to find out customer satisfaction at the bank of sulselbar the main branch of the city of palopo, and to determine the effect of Frontliner employee performance on customer satisfaction at Bank Sulselbar, the main branch of Palopo City. This research approach is quantitative. This research was carried outat the bank of sulselbar the main branch of the city of palopo. Sources of data in the study are customers at the main branch of the sulselbar bank in the city of palopoin december to january 2021. Data collection techniques in the form of observation, questionnaires (questionnaire), and documentation. Data analysis techniques in the form of validity test, reliability test, normality test, descriptive analysis, simple linear regression analysis, t test, correlation coefficient analysis, and analysis of the coefficient of determination. The results of the study indicate that the indicators used in each of these variables indicate where the employee's performance is in the very good category. Indicators on the customer satisfaction variable are in the very good category. Based on the correlation test, there is a strong/high relationship between the two variables. It can be concluded that there is an influence between Frontliner employee performance on customer satisfaction at Bank Sulselbar, the main branch of Palopo City